Uma escola para todos: quanto custa este direito? - Kunzler, Janaina (Universidade do Vale do Rio dos Sinos, 2019)
The discussion on the theme of inclusion has gained strenghtsince 1994, afterthe Declaration of Salamanca. This paper presents the idea of education in an inclusive perspective, leading to the urgent construction of a school for all (MANTOAN, 1999). In order to do so, it directs the discussion to the possibility of an inclusive school from the economic-financial point of view in private schools. It also addresses the complex question of equating the conditions of the Special Education offer in the regular network of private education, considering the pedagogical aspects, the management and financing of an Inclusive Education; thus, we discuss thedaily contrasts generateddue to the prohibition of the collection of additional values of inclusion students, provided for in the Brazilian Inclusion Law (LBI) and Technical Note 15 of the Ministry of Education (MEC). The research aims to determine the difference between cost-student and cost-student-inclusion, in light of the public policy of inclusion and the norms of inclusive education in force, aiming at fomenting a proposal of fiscal incentive and financing of the inclusion in the network of private education. The methodology applied was a Multiple Case Study (YIN, 2005), in which three regular private primary schools of the Municipality of Porto Alegre, Rio Grande do Sul, were investigated. Data were collected from July to September 2018, based on information of the year 2017. Interviews, forms and accounting documents were used as sources of evidence. In this study, the interviews were conducted spontaneously, with the purpose of ascertaining the institutional processes impacted by the inclusion of disabled students, with developmental disorder and high skills/giftedness in schools. For cost composition, the concept of economic cost was attributed, in which there is not always a value disbursement (MARQUES, 1996), but considers in the equation the amounts spent with working hours to perform such service. The index, considered an important management tool,was calculated based on the accounting information provided by the schools. A high percentage difference between cost-student and cost-student-inclusion was evidenced, as was the hypothesis of this research. It was identified that the student-inclusion index varies from school to school according to the characteristics of the services offered and the number of students enrolled. In all three cases, the index presented a cost-student-inclusion between 65% and 122% higher than cost-student. As a proposal for intervention, three actions were submitted: a) a suggestion to the State Board of Education of a review of the Parecer CEED/RS nº 056/2006 regarding the maximum number of students enrolled in classes with inclusion students, without interfere in the economic viability of institutions; b) referral of the research to the Public Prosecutor's Office of the Education Coordination of Porto Alegre, with the purpose of making known the costs entailed by inclusion in private institutions; c) conducting a tax incentive proposal for private institutions that have proven to meet the goals of special education students; d) to continue the advisory work, which I carry out, to the schools of the Doroteias Group, presenting the indicators of this dissertation as a possibility to increase their management tools. Thus, it is intended that the study provide changes in Brazilian public policies, in order to encourage private schools to expand the Special Education service without prejudice to the economic-financial sustainability of the school.
Keywords: Gestão educacional; Custos da Inclusão; Custo-aluno; Educational management; Costs of inclusion; Cost-student; ACCNPQ::Ciências Humanas::Educação